2020
DOI: 10.5747/10.5747/ca.2020.v16.n2.a374
|View full text |Cite
|
Sign up to set email alerts
|

Matéria orgânica como atenuante da salinidade da água de irrigação na cultura do milho

Abstract: The objective of this study was to evaluate the development of corn crop at different levels of irrigation water salinity in two concentrations of soil organic matter. The experiment was conducted at the Center for Agrarian Sciences of the Federal University of Alagoas. The experimental design adopted was the entirely randomized in factorial scheme 5 x 2, with four replications. The treatments consisted of different levels of electrical conductivity of CEa water (0,5; 1,5; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies have shown the positive effect of the use of organic sources in saline environments. Santos et al (2020) investigated the effect of the use of organic matter on maize crop growth under salinity and showed positive effects, including mitigation of saline stress. Similarly, Nascimento et al (2017) and Sousa et al (2017) demonstrated the benefit of the use of organic inputs in mitigating salt stress in sesame and yellow passion fruit crops irrigated with saline water and Santos et al (2019) demonstrated the same for bell pepper crops irrigated with saline water.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the positive effect of the use of organic sources in saline environments. Santos et al (2020) investigated the effect of the use of organic matter on maize crop growth under salinity and showed positive effects, including mitigation of saline stress. Similarly, Nascimento et al (2017) and Sousa et al (2017) demonstrated the benefit of the use of organic inputs in mitigating salt stress in sesame and yellow passion fruit crops irrigated with saline water and Santos et al (2019) demonstrated the same for bell pepper crops irrigated with saline water.…”
Section: Introductionmentioning
confidence: 99%